Investigating the Use of Assessment Data by Primary School Teachers: Insights from a Large-scale Survey in Ireland. Issue 3 (3rd July 2021) - Pitsia, Vasiliki; Karakolidis, Anastasios; Lehane, Paula
ABSTRACT: Evidence suggests that the quality of teachers' instructional practices can be improved when these are informed by relevant assessment data. Drawing on a sample of 1, 300 primary school teachers in Ireland, this study examined the extent to which teachers use standardized test results for instructional purposes as well as the role of several factors in predicting this use. Specifically, the study analyzed data from a cross-sectional survey that gathered information about teachers' use of, experiences with, and attitudes toward assessment data from standardized tests. After taking other teacher and school characteristics into consideration, the analysis revealed that teachers with more positive attitudes toward standardized tests and those who were often engaged in some form of professional development on standardized testing tended to use assessment data to inform their teaching more frequently. Based on the findings, policy and practice implications are discussed.